Meningkatkan kualitas bacaan dan hafalan anak melalui inisiatif pemuda Dusun Jorong Desa Sikur Barat dalam mendirikan (LTKQ) - Aulia Iswaratama (Prodi Tadris Matematika-UIN Mataram, 2021)
The existence of the qur 'an as a living guide is mandatory to be studied and taught for all mankind to have nothing more to gain the degrees of takwa and the salvation of the afterlife.So it is important to give knowledge and education about the qur 'an at an early age as a provision for children to print the generations of the qur 'ani.Early childhood is a golden age that results in rapid growth and growth. To create a generation of the qur 'ani that can understand and memorize the qur 'an, our village's jorong village west of sikur established an institute of tahfidz,and the study of the qur 'an,which is aimed at helping children improve reading and reciting the qur 'an,as well as teaching children basic religious science and educating them to be the ultimate discipline of time.